Voyager 2 Observations Near the Heliopause. (September 2020) - Richardson, John D.; Belcher, John W.; Burlaga, Leonard F.; Cummings, Alan C.; Decker, Robert B.; Opher, Merav; Stone, Edward C.
Abstract: This paper discusses plasma characteristics in the heliosheath region before the heliopause (HP), at the HP, and in the very local interstellar medium (VLISM). The Voyager 2 (V2) HP was a sharp boundary where the radial plasma currents went to background levels. The radial flow speeds derived from 53-85 keV (V1) and 28-43 keV (V2) ion data decreased about 2 years (8 AU) before the HP at V1 and V2. A speed decrease was not observed by the V2 plasma instrument until 160 days (1.5 AU) before the HP crossing when V2 entered the plasma boundary layer where the plasma density and 28-43 keV ion intensity increased. We determine the HP orientation based on the plasma flow and magnetic field data and show these observations are consistent with models predicting a blunt HP. Variations are observed in the currents observed in the VLISM; roll data from this region clearly show the plasma instrument observes the interstellar plasma and may be consistent with larger than expected VLISM temperatures near the HP.